Experimental studies into spectral and time characteristics of the accelerator U-12 radiation field - Yegorov, A.M.; Migalenja, V.Ja.; Nagaychenko, V.I.; Sotnikov, V.V.; Voronko, V.A.; Zhuk, V.V. (Вопросы атомной науки и техники, 2004)
The present paper is concerned with experimental studies of the structure, time and spectral characteristics of the radiation field of the accelerator U-12. The results obtained from the studies were used to develop the concept of constructing a mobile complex applicable for registration and location of neutron- and gamma-radiations outside the room, which accommodates the accelerator, and also for the assessment of efficiency in radiation shielding of pulsed accelerators.